(untitled) (TEST Antologia di Diritto Pubblico, 2023)
The article stems from a critical reading of the essay dedicated by Santi Romano to the investigation into the nature of Parliamentary Rules of Procedure. According to the Author, the essay still retains its considerable relevance for Constitutional studies and for reflections on the crisis of the system of the sources of law. Nevertheless, the breach opened by the essay in the dogmas of state sovereignty is not able to produce an accomplished reflection on the pluralism of the sources of law. This last, precisely, presupposes the recognition of the most varied forms of institutional, territorial, and social autonomy, which will only come about with the entry of the Constitution of the Italian Republic (1948).